2019
DOI: 10.1155/2019/7284040
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Inflammatory Markers in Predicting Hepatocellular Carcinoma Survival after Liver Transplantation

Abstract: Inflammatory markers have been studied in cancers and chronic states of inflammation. They are thought to correlate with tumor pathology through disruption of normal homeostasis. Markers such as neutrophil to lymphocyte ratio (NLR) among others have shown promise as prognostic tools in various cancers. In this study, we evaluate complete blood count based inflammatory markers in hepatocellular carcinoma (HCC) to predict overall and recurrence-free survival of patients after liver transplant. Between 2001 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…The removal of the chronically inflamed cirrhotic liver and the regaining of normal liver function, with recovery from the complications of liver failure and portal hypertension, contrast with a high surgical invasiveness, potentially severe surgical complications, and immunosuppressant toxicity [ 13 , 14 ]. However, the data assessing the post-transplant outcome in terms of inflammatory state are very limited [ 1 , 15 ], while data on the post-transplant metabolic recovery are extremely heterogeneous, variably reporting a significant increase in the prevalence of metabolic syndrome and an incomplete recovery from pre-LT sarcopenia [ 16 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The removal of the chronically inflamed cirrhotic liver and the regaining of normal liver function, with recovery from the complications of liver failure and portal hypertension, contrast with a high surgical invasiveness, potentially severe surgical complications, and immunosuppressant toxicity [ 13 , 14 ]. However, the data assessing the post-transplant outcome in terms of inflammatory state are very limited [ 1 , 15 ], while data on the post-transplant metabolic recovery are extremely heterogeneous, variably reporting a significant increase in the prevalence of metabolic syndrome and an incomplete recovery from pre-LT sarcopenia [ 16 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that predictors of HCC recurrence post LT have emerged, including AFP, microvascular invasion, platelet to lymphocyte ratio (PLR), lymphocyte to monocyte ratio (LMR), neutrophil to lymphocyte ratio (NLR) and systemic Immune-Inflammation Index (SII). [4][5][6] There is increasing evidence that correlates preoperative immunological statuses with not only postoperative complications but also long-term outcomes of patients with certain tumors, which is associated with poorer cancer-specific survival in patients with malignant tumors. [7][8][9] In addition, a growing number of studies have shown that circulating immune inflammatory cells such as platelets, neutrophils and lymphocytes play an important role in promoting the proliferation, invasion and migration of cancer cells by changing the tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation, both local (CRP) and systemic (ESR) has recently emerged as an important reflection of HCC aggressiveness and prognosticator. Various other clinical approaches have been taken to its measurement, including peripheral blood neutrophil to lymphocyte (NLR) and platelet to lymphocyte (PLR) ratios 21,33‐49 . These novel markers of disease activity are especially needed for that 50% of HCC patients who do not have elevated AFP levels 30,46,50 .…”
Section: Discussionmentioning
confidence: 99%
“…Various other clinical approaches have been taken to its measurement, including peripheral blood neutrophil to lymphocyte (NLR) and platelet to lymphocyte (PLR) ratios. 21,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] These novel markers of disease activity are especially needed for that 50% of HCC patients who do not have elevated AFP levels. 30,46,50 However, a central unanswered question is why elevated values of these inflammation markers predict poor survival.…”
Section: Discussionmentioning
confidence: 99%